Effect of feldspar addition into bioglass 45S5 composition: Crystallization kinetics and thermal transformation - Stábile, Franco Matías (2016)
Thermal transformations of glasses with formulations derived from Bioglass 45S5 with Al2O3 (≤2.5 wt %) and K2O additions through K-feldspar were studied. Crystallization kinetics and transformations were followed-up by X-ray diffraction and differential thermal analysis. The activation energy of crystallization of Na2CaSi2O6 was found to be lower than that of Bioglass 45S5 for the prepared samples. This behavior was attributed to an increase in phase separation in glasses. Nevertheless, transformations shifted towards higher temperatures with addition of feldspar, due to a decrease in pre-exponential factor. Cell parameters evolved progressively with increasing temperature without any abrupt changes. Al2O3 and K2O remained as a part of a residual glassy phase.